Investigation of the convex time budget experiment by parameter recovery simulation - Yuta Shimodaira; Kohei Shiozawa; Keigo Inukai (Osaka University, Institute of Social and Economic Research (ISER), 2022)
The convex time budget (CTB) method is a widely used experimental method for eliciting an individual's time preference. Researchers adopting the CTB experiment usually assume quasi-hyperbolic discounting utility as a behavioural model and estimate the parameters of the utility function. However, few studies using the CTB method have examined parameter recovery. We conduct simulations and find that the estimation error of the present bias parameter is so large that its effect is difficult to detect. The large error is due to the improper combination of the experimental method and the utility model, and it is not a problem we can deal with after the data collection. This paper suggests the importance of running parameter recovery simulations to audit estimation errors in the experimental design.
Keywords: 330; Intertemporale Entscheidung; Statistische Methode; Experiment; Systematischer Fehler; Simulation; Theorie